The Relationship of Husband and Wife in Qs. Al-Nisa' Ayat 34 Perspective of Ibnu 'Ashur and Wahbah Al-Zuhaily - Imron Rosyidi; Masrifatul Jannah (Penerbit Hellow Pustaka, 2025)
Surah Al-Nisa' verse 34 contains an explanation of husband and wife in household life, but household life that should be sakinah, mawaddah wa rahmah is difficult to achieve because of the lack of balance between husband and wife in carrying out their respective rights and obligations, which causes problems in the household. This study was conducted to describe the views of Ibn 'Ashur and Wahbah Al-Zuhaily regarding the relationship between husband and wife in the interpretation of QS. Al-Nisa' verse 34 using the library method and comparing two contemporary tafsir books, namely Tafsir al-Tahrir wa al-Tanwir and Tafsir al-Munir. The interpretations of Ibn 'Ashur and Wahbah Al-Zuhaily have the same view regarding the Relationship between Husband and Wife in QS. Al-Nisa' verse 34, namely that men as husbands become leaders, protectors, and educators for their wives and carry out their rights and obligations well, such as in terms of providing a living and protection. It's just that Ibn 'Ashur's interpretation is more patriarchal and Wahbah Al-Zuhaily's interpretation is more gender-just. And women as wives are required to carry out their rights and obligations well, namely by becoming a wife who is pious, faithful and hafizah lil Ghaib